2007
DOI: 10.1007/s10552-007-9009-5
|View full text |Cite
|
Sign up to set email alerts
|

Lack of evidence for effect modification by estrogen of association between body mass index and colorectal cancer risk among postmenopausal women

Abstract: Our results do not support the hypothesis that BMI increases risk of colorectal cancer more strongly among women with higher levels of estrogen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…Contrary to our results, these studies have found a stronger association in premenopausal or estrogen-positive women than in postmenopausal or estrogen-negative women. Other studies have, however, not found the effect of BMI to be modified by use of hormone replacement therapy (HRT) in postmenopausal women (42,43). We could not study effect modification by HRT.…”
Section: Discussionmentioning
confidence: 79%
“…Contrary to our results, these studies have found a stronger association in premenopausal or estrogen-positive women than in postmenopausal or estrogen-negative women. Other studies have, however, not found the effect of BMI to be modified by use of hormone replacement therapy (HRT) in postmenopausal women (42,43). We could not study effect modification by HRT.…”
Section: Discussionmentioning
confidence: 79%
“…(25, 26) While similar associations have also been reported for endometrial cancer (27, 28), evidence for effect modification for colorectal cancer is inconsistent across studies. (29, 30)…”
Section: Discussionmentioning
confidence: 99%
“…A positive association of BMI and CRC risk was not found among HRT users (Po0.01). Recently, another large cohort study from the United States including 814 incident cases with CRC observed a statistically significant increase in CRC risk among nonusers of hormones with BMIX30 kg m À2 (HR 1.36, 1.04 -1.79), but not among users, when compared to women with BMIo25 kg m À2 (Wang et al, 2007). However, despite the size of the study, no significant effect modification of the BMI -CRC association was found for never, former, and current use of HRT (P ¼ 0.5).…”
Section: Discussionmentioning
confidence: 99%
“…However, despite the size of the study, no significant effect modification of the BMI -CRC association was found for never, former, and current use of HRT (P ¼ 0.5). Except for the WHS and the study by Wang et al (2007), all other previous studies differentiating between users and nonusers of HRT were mainly reporting on colon cancer risk (Slattery et al, 2003;Hou et al, 2006;Pischon et al, 2006;Adams et al, 2007), so we repeated the analysis after exclusion of patients with rectum cancer (32% of cases). Despite the limited power, ORs were similar for all BMI groups and risk of CRC was still significantly increased in the two highest BMI groups among those with no HRT use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation